Cover Picture: Plasma Process. Polym. 2∕2014. Issue 2 (February 2014) - Macias‐Montero, Manuel; Borras, Ana; Romero‐Gomez, Pablo; Cotrino, Jose; Frutos, Fabian; Gonzalez‐Elipe, Agustin R.
<x xml:space="preserve">Abstract</x> Front Cover: Low temperature plasma deposition of TiO2 on silver layers and nanoparticles provides the formation of vertical or tilted Ag@TiO2 core@shellnanorods. The cover picture gathers a SEM image of Ag@TiO2 nanorods with an inset of backscattered electron signal showing the inner distribution of silver. A photograph of a water droplet with high contact angle and the evolution of the WCA under UV light are also presented in the cover picture. Further details can be found in the article by Ana Borras et. al. on page 164. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>